D-dimer levels in non-COVID-19 ARDS and COVID-19 ARDS patients: a systematic review with meta-analysis - Tóth, Krisztina; Fresilli, Stefano; Paoli, Nicola; Maiucci, Giacomo; Salvioni, Mariateresa; Kotani, Yuki; Katzenschlager, Stephan; Weigand, Markus A.; Landoni, Giovanni (PLOS ONE, 2023)
Background Hypercoagulability and thrombo-inflammation are the main reasons for death in COVID-19 patients. It is unclear whether there is a difference between D-dimer levels in patients without or with COVID-19 acute respiratory distress syndrome (ARDS). Methods We searched PubMed, EMBASE, and ClinicalTrails.gov databases looking for studies reporting D-dimer levels in patients without or with COVID-19 ARDS. Secondary endpoints included length of hospital stay, and mortality data at the longest follow-up available. Results We included 12 retrospective and 3 prospective studies with overall 2,828 patients, of whom 1,404 (49.6%) had non-COVID-19 ARDS and 1,424 had COVID-19 ARDS. D-dimer levels were not significantly higher in non-COVID-19 ARDS than in COVID-19 ARDS patients (mean 7.65 mg/L vs. mean 6.20 mg/L MD 0.88 [CI: -0.61 to 2.38] p = 0.25; I² = 85%) while the length of hospital stay was shorter (non-COVID-19 mean 37.4 days vs. COVID-19 mean 48.5 days, MD -10.92 [CI: -16.71 to -5.14] p < 0.001; I² = 44%). No difference in mortality was observed: non-COVID-19 ARDS 418/1167 (35.8%) vs. COVID-19 ARDS 467/1201 (38.8%). Conclusions We found no difference in the mean D-dimer levels between non-COVID-19 ARDS and COVID-19 ARDS patients.